Bioretention soil capacity for removing nutrients, metals, and polycyclic aromatic hydrocarbons; roles of co-contaminants, pH, salinity and dissolved organic carbon. (15th December 2022) - Esfandiar, Narges; McKenzie, Erica R.
Abstract: Conventional bioretention soil media (BSM: e.g., loamy sand) is employed in infiltration-based stormwater management practices, but concerns exist on its limited sorption capacity. However, limited quantitative data is available, particularly considering the wide range of contaminants and water quality conditions that occur in stormwater. This study utilized batch tests to investigate the capability of conventional BSM for simultaneous removal of three nutrients (ammonium, nitrate, and phosphate), six metals (Cd, Cr, Cu, Ni, Pb and Zn), and four polycyclic aromatic hydrocarbons (PAHs: naphthalene, acenaphthylene, phenanthrene, and pyrene) from synthetic stormwater. Moreover, the effects of co-contaminants and different stormwater chemistry parameters (pH, salinity, and dissolved organic carbon (DOC)) on BSM sorption capacity were investigated. BSM was not effective for nutrients removal; however, it had good removal efficiency for metals such as Cu, Pb, and Cr which are less soluble at neutral pH values compared to metals such as Ni, Cd and Zn. Moreover, BSM was effective for removing PAHs with higher hydrophobicity such as pyrene and phenanthrene. Metals sorption capacity of BSM was greater at higher pH, lower salinity and DOC; however, the sorption capacity of BSM for PAHs was not sensitive to stormwater chemistry parameters. However, competitive sorption had a notable effect on low molecular weight PAHs, Cd, and Ni. This study provides a quantitative evaluation of the BSM performance and compares the sorption capacity to potential sorptive amendments used in stormwater management. While select sorbent amendments out-performed the BSM, this was not universal and was contaminant specific; careful consideration of water quality enhancement goals and solution chemistry are required in selecting a sorbent. Overall, this study identifies the possible limitations in BSM compositions and factors that may adversely affect BSM sorption capacity, and finally describes options to enhance BSM performance and recommendations for future research. Highlights: The coexistence of contaminants affected the sorption capacity of soil media. Sorbent affinity for Cr, Cu & Pb was higher than Cd, Ni & Zn in mixed solutions. Among PAHs, more hydrophobic PAH had higher affinity to sorbent in mixed solutions. Conventional bioretention soil media was not effective for nutrients removal. Water quality parameters had no significant effect on PAHs sorption process.